Activation mechanism of Fe (III) ions in cassiterite flotation with benzohydroxamic acid collector. (April 2018) - Tian, Mengjie; Liu, Runqing; Gao, Zhiyong; Chen, Pan; Han, Haisheng; Wang, Li; Zhang, Chenyang; Sun, Wei; Hu, Yuehua
Highlights: Fe (III) ions can be used as the activator in cassiterite flotation. Oterm atoms of cassiterite surface are the dominant active sites for Fe (III) ion adsorption. There are two possibilities for BHA adsorption in the presence of Fe (III) ion activator. Abstract: Pb 2+ ions are commonly used as the activator in the flotation of cassiterite. However, lead pollution of surface water has attracted more concern and attention. In this study, the effect of Fe 3+ ions as an activator on the flotation performance of cassiterite using benzohydroxamic acid (BHA) as the collector was investigated by the micro-flotation tests. The results of the flotation experiments showed that the addition of Fe 3+ ions significantly increased the recovery of cassiterite in the presence of BHA collector. In the BHA flotation of cassiterite, there was a direct relationship between the recovery of cassiterite and the adsorption amount of BHA on the cassiterite surface. The adsorption mechanism of BHA on un-activated and Fe-activated cassiterite surfaces was studied by the adsorption experiments, zeta potential measurements, and X-ray photoelectron spectroscopy (XPS) analysis. The results of the adsorption and zeta potential experiments indicated that the adsorption amount of BHA on the cassiterite surface increased significantly in the presence of Fe 3+ ions. The XPS analysis also revealed that terminal hydroxyl group oxygen atoms of the cassiterite surface were the dominant reactive sites for Fe 3+ ion adsorption. Furthermore, BHA anions can react with Fe atoms adsorbed on the cassiterite surface to form Fe-BHA complexes, thus improving the hydrophobicity of the cassiterite surface.